Solving the vehicle routing problem by a hybrid meta-heuristic algorithm - Majid Yousefikhoshbakht; Esmaile Khorram (Journal of Industrial Engineering International, 2012)
The vehicle routing problem (VRP) is one of the most important combinational optimization problems that has nowadays received much attention because of its real application in industrial and service problems. The VRP involves routing a fleet of vehicles, each of them visiting a set of nodes such that every node is visited by exactly one vehicle only once. So, the objective is to minimize the total distance traveled by all the vehicles. This paper presents a hybrid two-phase algorithm called sweep algorithm (SW) + ant colony system (ACS) for the classical VRP. At the first stage, the VRP is solved by the SW, and at the second stage, the ACS and 3-opt local search are used for improving the solutions. Extensive computational tests on standard instances from the literature confirm the effectiveness of the presented approach.
Keywords: 650; ant colony system; NP-hard problems; sweep algorithm; vehicle routing problem